A Study on the Problems in Teaching English Listening Skills to the 10th form Students at Phu Ly B High School and some Suggested Solutions - Vũ, Thị Thanh Hương (University of Languages and International Studies, 2017)
Chapter 1: Literature review –provides some theoretical background a bout listening comprehension, teaching listening skill and problems with listening activities. Chapter 2: Methodology –presents the current situation of teaching and learning listening at PB school. This chapter also deals with the introduction of the research methods which cover research questions, the participants and data collection instruments. Chapter 3: Data analysis and discussions –presents the data results, analysis collected from two questionnaires as well as the interviews. Chapter 4: Findings and suggestedsolutions –concludes the findings the researcher has from the study and proposes some solutions to the teaching of ELS to 10th form students in PB school.